Matrioskas de ficção: The Nothingness Club, de Edgar Pêra - Sousa, Rui (Pessoa Plural)
The Nothingness Club – O Clube do Nada (2023) is likely Edgar Pêra’s most comprehensive and profound exploration of Fernando Pessoa’s rich and multifaceted universe, with its seemingly boundless network of meanings and interpretative possibilities. This paper discusses some processes related to the question of authorship, focusing on two main axes: the relationship between Pessoa’s perspectives on his authorial project and how it is redefined in the film; and the way the filmic reinterpretation of figures and key elements of Pessoa's life and work contribute to a certain estrangement regarding the poet’s principles, leading at times to ambiguous reactions from the audience. I propose an examination of certain reading habits shaped by the weight of Pessoa’s programmatic and self-reflective texts, and how these habits continue to influence much of the critical tradition dedicated to his work.